PREDICTION OF CONVERGENCE VALUES IN SHALLOW TUNNELS WITH VARIOUS SUPPORT SYSTEMS FOR POOR ROCK MASS CLASS (RMR = 21-40) - Adzan Aulia Amin, Muhammad
This study focuses on predicting the convergence values of shallow tunnels in poor rock mass conditions (RMR 21-40), aiming to predict tunnel convergence values at various depths for each support system and provide optimal recommendations for selecting the appropriate support system at each depth. The study examines the horizontal deformation response of tunnels to in situ pressure and the characteristics of supports such as h-beam, rockbolt, and shotcrete. This analysis is conducted through 2D numerical modeling using RS2 software. The results indicate that one tunnel model with the Support 1 system at a depth of 60 meters is in an unsafe condition, with convergence values exceeding the tolerated safety limits. Support 4 is identified as a support system that can enhance tunnel stability up to a depth of 60 meters, whereas other support systems exhibit instability at shallower depths. This finding is reinforced by an analysis using the P-M Diagram (Eurocode 1992-1), which evaluates the capacity of support systems to withstand bending moments and axial forces at different depths. To reduce the risk of deformation and ensure tunnel stability, this study suggests that the support system should consider increasing support pressure with depth, especially under poor rock mass conditions.